Can the Law Affect Attitudes and Behaviour in the Absence of Strict Enforcement? Experimental Evidence from a Child Marriage Reform in Bangladesh - Amrit Amirapu; Niaz Asadullah; Zaki Wahhaj (Institute of Labor Economics (IZA), 2024)
In developing countries, one in four girls is married before turning 18, with adverse consequences for themselves and their children. In this paper, we investigate whether laws can affect attitudes and behaviour towards child marriage –in a context in which the laws are not strictly enforced. We do so by developing a simple theoretical model of marriage age choice which allows us to account for several potential mechanisms through which a change in the formal law may affect attitudes and behaviour even when the law is not enforced. We also implement a randomised video-based information intervention that aimed to accelerate knowledge transmission about a new child marriage law in Bangladesh that introduced harsher punishments for facilitating early marriage. Surveys conducted immediately after the intervention document changes in respondents' attitudes while follow-up surveys conducted several months later document an increase in early marriage among treated households if the father or family elders also received the information. The findings allow us to distinguish between several competing theoretical channels underlying the effect of legal change and highlight the risk of backlash against laws that contradict traditional norms and practices.
Keywords: J12; J16; K36; 330; age of marriage; social norms; formal institutions; legal change